Analisis Tingkat Keramahan Lingkungan Alat Tangkap Pukat Cincin (Purse Seine ) di Perairan Kabupaten Buleleng Provinsi Bali - Ferdiansah Rukmana; M Tajuddin Noor; Exist Saraswati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Purse seine is one of the most commonly used fishing gears in pelagic fisheries due to its high efficiency in catching large quantities of fish. However, to ensure the sustainability of fish resources and marine ecosystems, its use must comply with the principles of the Code of Conduct for Responsible Fisheries (CCRF), which emphasizes responsible and environmentally friendly fishing practices. This study aims to analyze the environmental friendliness level of purse seine fishing gear, with a focus on its operation in Bali waters. The methods used in this study included field observations, interviews with fishermen, and literature review from various sources related to sustainable fisheries. Purse seine is widely operated in the waters of Bali, particularly using a single boat system. Data were collected through interviews with 30 respondents. The study revealed that the total catch obtained by fishermen in the waters of Buleleng Regency, Bali Province reached 18,436 tons. The findings suggest that while purse seine fishing is highly productive, its sustainability is dependent on adhering to responsible fishing practices that minimize negative environmental impacts, ensuring the long-term viability of marine ecosystems and fish populations.